Multimodal Air Freight Forwarding Strategy in Overcoming the Post-Pandemic International Cargo Capacity Crisis - Ningseh, Putri Wahyu; Tohir, Muhammad (Siber Journal of Transportation and Logistics, 2025)
This study examines air cargo capacity management strategies in the post-COVID-19 era, focusing on the role of multimodal air freight forwarding. The imbalance between rising shipment demand and limited carrying capacity remains a major challenge for the global logistics industry. The study aims to analyze the impacts of the air cargo capacity crisis, assess multimodal strategies as adaptive solutions, and explore capacity management challenges in Indonesia. A descriptive qualitative method was applied using literature study, based on secondary data from international institution reports, academic journals, and national statistics. The results show that integrating sea, land, and air modes supported by data-driven management systems improves the efficiency of global air cargo capacity management. At the national level, strengthening domestic multimodal infrastructure is essential for enhancing capacity management efficiency in Indonesia. This research contributes to industrial engineering development in adaptive data-based multimodal logistics capacity management.